Proceedings of the 1st All-Russian Congress of the Russian Association of Therapeutic Radiation Oncologists (RATRO) "New technologies in radiotherapy and nuclear medicine. Development prospects " 27-28 April 2017 - Editorial Article (Исследования и практика в медицине, 2017)
.